Usefulness of natriuretic peptide for the diagnosis of Kawasaki disease: a systematic review and meta-analysis. Issue 4 (14th April 2015) - Lin, Kuan-Ho; Chang, Shy-Shin; Yu, Chin-Wei; Lin, Shen-Che; Liu, Shu-Chun; Chao, Hsiao-yun; Lee, Meng-tse Gabriel; Wu, Jiunn-Yih; Lee, Chien-Chang
Abstract : Objective: To examine the diagnostic value of serum B-type natriuretic peptide (BNP) in acute Kawasaki disease (KD). Design: Systematic review and meta-analysis. Data sources: A systematic literature search strategy was designed and carried out using MEDLINE, EMBASE and the Cochrane Library from inception to December 2013. We also performed manual screening of the bibliographies of primary studies and review articles, and contacted authors for additional data. Study eligibility criteria: We included all BNP and NT-pro (N-terminal prohormone) BNP assay studies that compared paediatric patients with KD to patients with febrile illness unrelated to KD. We excluded case reports, case series, review articles, editorials, congress abstracts, clinical guidelines and all studies that compared healthy controls. Primary and secondary outcome measures: The performance characteristics of BNP were summarised using forest plots, hierarchical summary receiver operating characteristic (ROC) curves and bivariate random effects models. Results: We found six eligible studies including 279 cases of patients with KD and 203 febrile controls. Six studies examined NT-proBNP and one examined BNP. In general, NT-proBNP is a specific and moderately sensitive test for identifying KD. The pooled sensitivity was 0.89 (95% CI 0.78 to 0.95) and the pooled specificity was 0.72 (95% CI 0.58 to 0.82). The area under the summary ROC curve was 0.87 (95% CI 0.83 to 0.89). The positive likelihood ratio (LR+ 3.20, 95% CI 2.10 to 4.80) was sufficiently high to be qualified as a rule-in diagnostic tool in the context of high pre-test probability and compatible clinical symptoms. A high degree of heterogeneity was found using the Cochran Q statistic. Conclusions: Current evidence suggests that NT-proBNP may be used as a diagnostic tool for KD. NT-proBNP has high diagnostic value for identifying KD in patients with protracted undifferentiated febrile illness. Prospective large cohort studies are needed to help determine best cut-off values and further clarify the role of NT-proBNP in the diagnosis process of KD.